Making sense of visual management through affordance theory. Issue 2 (25th January 2017) - Beynon-Davies, Paul; Lederman, Reeva
Abstract: Visual management is much used within operations management practice, particularly in association with process improvement initiatives in diverse areas such as production and healthcare. The practitioner literature abounds with suggested best practice. However, there is little attempt to theorise about why the design and use of 'visual' devices for such process improvement works in practice. Within this paper we describe a novel theory of operation which highlights the role that material and visual artefacts proposed by visual management practitioners play within particular ways of organising work. We develop an innovative way of employing the theory of affordances to explain how first- and second-order affordances, situated around the visual devices at the heart of visual management, connect three domains of action, which we refer to as articulation, communication and coordination. Our analysis of three cases from healthcare, clothing manufacturing and software production help ground the theorisation discussed.